"TASTE THIS VIDEO!": FACEBOOK VIDEOS AS EMBODIED EXPERIENCES. - Schlussel, Hadas; Frosh, Paul (AoIR Selected Papers of Internet Research, 2020)
Videos are among the most widely used media formats on Facebook. Yet little research has been done on their aesthetic and formal attributes, and especially on how they operate within the frameworks of attention, interruption and embodied interaction specific to social media interfaces. This paper examines recipe videos published on Tasty, one of the most popular Facebook pages in the world. We analyze these videos through a novel three-dimensional model that integrates their semiotic characteristics (visual, auditory and textual), their interactive and haptic qualities, and their invitation to perceptual engagement and sensorimotor response. We conclude that Facebook recipe videos are exemplary of a broader category of social media videos which we call hyper-sensory videos: these create heightened multisensory experiences that take precedent over informational use or narrative involvement, revealing the deeply physical character of our connections to social media and a yearning for embodied presence in what we might call our online-life.